Organizational facilitators and barriers for participation in workplace health promotion in healthcare: A qualitative interview study among nurses - Bleier, Hannah; Lützerath, Jasmin; Schaller, Andrea (Frontiers in Psychology, 2023)
Background: Although there are indications for positive effects of Workplace Health Promotion (WPH) in the highly burdened profession of nurses and this target group actively desires it, the number of participants is low. Individual reasons play a role in the decision to engage in WHP activities, yet it is interesting to consider which organizational factors a company could actually address to improve participation. In this regard, the question arises what organizational factors facilitate participation in WHP activities from the perspective of nurses in inpatient care facility (ICF), outpatient care service (OCS) and acute care hospitals (ACH). Method: Sixteen semi-structured interviews were conducted in the different care settings between May and September 2021. Questions about the everyday working life, WHP activities and organizational framework conditions were asked. Result: The results show that there is a wide range of influencing factors at the organizational level, some over all settings, others setting-specific. High workload and the fit of WHP activities with shift times were particularly inhibiting over all settings. A negative association with the employer worked as a barrier in ICF and ACH. Conclusion: When implementing WHP activities, it can be useful to consider organizational facilitators and barriers to promote sustainable and attractive WHP activities and higher participation rates in the different settings of nursing.